Chinese Rush to Africa: Comparative Historical Analysis - E. I. Zelenev; M. A. Soloshcheva (Сравнительная политика, 2020)
In this article, the authors conduct a comparative historical analysis of the stages of Chinese penetration into Africa, the concepts, goals, means, methods and consequences of this penetration for China itself and for individual African countries. The authors conclude that compared to the period of twenty years ago, when China began to show increased interest in Africa, a new situation has now emerged. China has created a binary structure: the Forum of China-Africa cooperation launches a mechanism for selecting countries that are ready to follow the political path of the PRC with the prospect of becoming a country-follower of China, and the “One belt – one road” program de facto “forms membership” in the club of countries-followers of China, fixing these countries in the trail of Chinese influence not only politically, but also economically.